The Influence of Perceived Ease of Use and Perceived Usefulness on the Behavioral Intention of QRIS Users in Gorontalo - Muhammad, Fadel; Asnawi, Melan Angriani; Niode, Idris Yanto (International Journal of Economics and Business Management, 2025)
Interoperability is a vital strategic component in the digital payment ecosystem in Indonesia, and QRIS is a concrete manifestation of this strategic project. This study aims to analyze the influence of Perceived Ease of Use (PEOU) and Perceived Usefulness (PU) on the Behavioral Intention of QRIS users. This study uses a quantitative approach with a survey method. The research sample consisted of 96 respondents who are QRIS users in Gorontalo City, determined through a purposive sampling technique. Data were collected using a Likert-based questionnaire, then analyzed using multiple linear regression using SPSS. The results show that PEOU and PU have a significant effect on the Behavioral Intention of QRIS users. In addition, both technology acceptance variables simultaneously drive Behavioral Intention with a significance value of 82.5%, indicating the significant influence of this technology acceptance among the Gorontalo community